Sex, Race, and the Adverse Effects of Social Stigma vs. Other Quality of Life Factors Among Primary Care Patients with Moderate to Severe Obesity - Wee, Christina C. (J Gen Intern Med, 2014)
BACKGROUND: Patients with obesity face widespread social bias, but the importance of this social stigma to patients relative to other quality of life (QOL) factors is unclear. OBJECTIVE: Our aim was to examine the importance of obesity-related social stigma relative to other QOL factors on reducing patients’ overall well-being. DESIGN: We used a cross-sectional telephone interview. SETTING: The study was conducted at four diverse primary care practices in Greater Boston. PARTICIPANTS: Three hundred and thirty-seven primary care patients aged 18–65 years and with a body mass index (BMI) of 35 kg/m(2) or higher participated in the study. MAIN MEASURES: Patients’ health utility (preference-based QOL measure) was determined via responses to a series of standard gamble scenarios assessing willingness to risk death to lose various amounts of weight or to achieve perfect health. We used the Impact of Weight on Quality of Life-lite instrument to assess QOL domains specific to obesity (physical function, self-esteem, sexual life, public distress or social stigma, and work), and we examined variation in utility explained by these domains. KEY RESULTS: Depending on patients’ race/ethnicity, mean health utilities ranged from 0.92 to 0.99 among men and from 0.89 to 0.93 among women. After adjustment for race, BMI, and education, none of the QOL domains explained much of the variation in utility among men, except for work function among Hispanic men. In contrast, social stigma was the leading QOL contributor to utility for Caucasian women (explaining 6 % of the marginal variation beyond demographics and BMI). In contrast, sexual function was the most important contributor among African American women (3 % marginal variation), and work life was most important among Hispanic women (> 20 % in variation). Lower scores in one domain did not always translate into lower well-being. Moreover, QOL summary scores often explained less of the variation than some individual domains. CONCLUSION: Obesity-related social stigma had disproportionate adverse effects on Caucasian women patients’ well-being, whereas weight-related impairment in work function was particularly important among Hispanic patients and impaired sexual function was important to diminished well-being among African American women although its impact appeared modest.